Impact of accelerating admixtures on the electrical properties of ordinary portland cement pastes. (October 2022) - Montanari, Luca; Helsel, Michelle; de la Varga, Igor; Spragg, Robert; Juenger, Maria
Abstract: Electrical resistivity is a reliable concrete testing tool that agencies, researchers, and contractors have adopted to quickly assess the transport properties of cementitious systems. Like other electrically-based tests, resistivity measurements can be influenced, among other factors, by the ions dissolved in the pore solution of cementitious systems. To isolate the pore solution component, some researchers have suggested the implementation of the formation factor, which accounts for the system's pore solution. Among the mixture constituents potentially affecting the pore solution, accelerating admixtures are thought to have significant effects. Due to the lack of pore solution data, the community has come to mistrust any electrically-based test performed on concrete mixtures that include this kind of admixture. This study aims to improve the understanding of the effect that four different types of accelerating admixtures have on the electrical properties of an ordinary portland cement paste system. The data show that the influence of accelerating admixtures on the pore solution lessens over time. Moreover, development rates in the degree of hydration and the porosity of the system are found to be significantly affected by the chemistry of the admixture. Both electrical resistivity and formation factor are found to have high correlation with the total porosity of systems with and without accelerating admixtures.